Roman Campaigns and Negotiations in the East, 542–545 - Greatrex, Geoffrey (Studia Ceranea, 2021)
This article seeks to support the earlier dating of campaigns on the Roman eastern frontier in the 540s. It addresses points made in a recent contribution by Michael Whitby, who argued that the traditional chronology, which places a Roman invasion of Persarmenia in 543 and a Persian siege of Edessa in 544, should be retained. The article seeks to demonstrate that the grounds he offers are inadequate and concludes therefore that the earlier dating, according to which the Romans invaded Persarmenia in autumn 542 and the Persians besieged Edessa in 543, is to be preferred.